Pengaruh Hutang Terhadap Profitabilitas Industri Semen yang Terdaftar di Bursa Efek Indonesia - Herman Sjahruddin; Nurwahida Nurwahida (Jurnal Ecogen, 2021)
We are working again to test the influence of DAR and DER on ROA in the Cement Industry sector in 2015-2019 is the purpose of this study. Financial statements as a database are then drawn into samples. And a sample of 6 Cement Industry companies listed on the Indonesia Stock Exchange and using a quantitative approach. The data anlysis unit based on a sample of 90 units of data processed uses multiple regression analysis through SPSS Version 25. The type of data in these findings is quantitative data. Data is collected using time series data. The results obtained from this study provide evidence that low DAR is able to make ROA increasing. On the other hand, although a low DAR will provide a good thing because in addition to providing high ROA, this also provides evidence that the productivity it has is able to attract investors to invest.ini indicates that the DAR has a significant negative effect, meanwhile the DER has a insignificant positive effect on ROA.